Semiotic Analysis of Grab and OVO Identity on Instagram - Naspia, Wika; Adawiyah, Hilda; Normawati, Wahyu Putri; Fandra, Fadhilla Izzatul; Fauziah, Kholifatul (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2025)
This research aims to analyze how Grab and OVO visual identities communicate through Instagram. The research was conducted with a qualitative approach using Roland Barthes' semiotic model on the visual elements of Instagram content in the form of illustrations, colors, typography, and layout. Grab and OVO Instagram content uploaded from October 2024 to December 2024 became the unit of analysis of this research. Documentation of the unit of analysis and secondary data were conducted as data collections techniques. The results show that the characteristics of Gran and OVO visual identity through Instagram content are effective. This can be seen from the consistency of the visual characteristics that are built, namely the characteristics of color, typography, and layout. In addition, the visual identity of Gran and OVO in communicating is conveyed through content uploaded on Instagram, interestingly they also use uniques illustrations, and various content with trending topics.